The Composition of the Chemicals, Antioxidants, and Anti-Microbial Agents on the Essential Oil of the Piper Species and Its Potential as A Natural Preservative: A Review - Rina Susanti; Sukardi Sukardi (The University of Lampung, 2023)
The production of safe food with a little to no artificial preservatives is the main and most important challenge for the food manufacturing industry. Increasing demand of using the safe preservatives has pushed the food industry to use the herbal or natural preservatives. The essential oil of the piper species consists of complex compounds like the monoterpene that has a power in the activity of the antioxidant and antibacterial. The object of research is the essential oil of piper species like the Piper nigrum, Piper betle, Piper retrofractum, Piper caninum, and Piper cubeba. The review methodology used in this research is the PRISMA flowchart (2020). PRISMA aims to identify the quality of papers and transparency of the number of articles. The objective of this research is to summarize the research related to the chemical content of the piper essential oil, the antioxidant and anti-microbe as the potential natural preservatives. The anti-microbe activity on the piper species shows the MIC score ranging from 1.5 to 12.8 mg/mL towards the standard of bacterial preservatives in preventing pathogens in foods. The essential oil of piper species has the higher antioxidant compared to the synthetic ones, like the BHA and BHT that have the score of IC₅₀ <50 mg/mL. The essential oil of piper species has the GRAS certification and “safe” as an additive in foods. Keywords: DPPH, Monoterpene, MIC, Sesquiterpene.